Complete Versus Staged Repair for Neonates With Tetralogy of Fallot: Establishment and Validation of a Cohort of 2235 Patients Using Detailed Surgery Sequence Review of Health Care Administrative Data. Issue 11 (November 2018) - Savla, Jill J.; Fisher, Brian T.; Faerber, Jennifer A.; Huang, Yuan-Shung V.; Mercer-Rosa, Laura
Abstract : Background: The surgical strategy for neonates with tetralogy of Fallot (TOF) consists of complete or staged repair. Assessing the comparative effectiveness of these approaches is facilitated by a large multicenter cohort. We propose a novel process for cohort assembly using the Pediatric Health Information System (PHIS), an administrative database that contains clinical and billing data for inpatient and emergency department stays from tertiary children's hospitals. Methods: A 4-step process was used to identify neonates with TOF: (1) screen neonates in PHIS with International Classification of Diseases-9 (ICD-9) diagnosis or procedure codes for TOF; (2) include patients with TOF procedures before 30 days of age; (3) exclude patients with missing 2-year follow-up data; (4) analyze patients' 2-year surgery sequence patterns, exclude patients inconsistent with a treatment strategy for TOF, and designate patients as complete or staged repair. Manual chart review at 1 PHIS center was performed to validate this process. Results: Between January 2004 and March 2015, 5862 patients were identified in step 1. Step 2 of cohort assembly excluded 3425 patients (58%); step 3 excluded 148 patients (3%); and step 4 excluded 54 patients (1%). The final cohort consisted of 2235 neonates with TOF from 45 hospitals. Manual chart review of 336 patients showed a positive predictive value for accurate PHIS identification of 44% after step 1 and 97% after step 4. Conclusions: This systematic cohort identification algorithm resulted in a high positive predictive value to appropriately categorize patients. This carefully assembled cohort offers a unique opportunity for future studies in neonatal TOF outcomes. Abstract : Supplemental Digital Content is available in the text.